3(2)+29x-10=0

Simple and best practice solution for 3(2)+29x-10=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2)+29x-10=0 equation:


Simplifying
3(2) + 29x + -10 = 0

Multiply 3 * 2
6 + 29x + -10 = 0

Reorder the terms:
6 + -10 + 29x = 0

Combine like terms: 6 + -10 = -4
-4 + 29x = 0

Solving
-4 + 29x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 29x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 29x = 0 + 4
29x = 0 + 4

Combine like terms: 0 + 4 = 4
29x = 4

Divide each side by '29'.
x = 0.1379310345

Simplifying
x = 0.1379310345

See similar equations:

| 6n^2-7n-10= | | -7d+8=-76 | | 7n+5=-23 | | 5k-8=32 | | 7x(x-5)=5(4-3) | | 6+7w=-15 | | -6-6b=-66 | | 3t-6=-6 | | 8y+8=15y+8 | | -1-5w=-1 | | 6t-3=-69 | | 5b-5=0 | | 7k+3=31 | | 2t+9=13 | | 2-5d=-18 | | 9+5b=64 | | 4x^2+24=104-x^2 | | 4x(2)+27x-7=0 | | 6(x+4)+3x=4(x-2) | | -10+4b=-50 | | 5-7n=-44 | | 10+4b=54 | | 2a+3=-13 | | -7b+8=-62 | | 2k-10=-28 | | 13.7t-4.7=9.9+81t | | -5a+6=-14 | | -3m+9=36 | | 4k+3=47 | | -5x/6/2 | | 7a+8=15 | | -7m+4=-38 |

Equations solver categories